1936
DOI: 10.1002/ange.19360494603
|View full text |Cite
|
Sign up to set email alerts
|

Über die Verfärbung des Zinksulfids im Licht

Abstract: Xach eiiiem Vortrag in der E'achgruppe fur Aiioaganische Cheniie auf der 45. HauptvcrsaiiiiiiluiiS des V D Ch. in Konigsberg am 5 . Juli 1935.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…However, the waste is concentrated at the end of such 18 treatments instead of undergoing complete annihilation [1]. Then, 19 this concentrated waste is either incinerated or dumped on land 20 contributing to another type of pollution. The same is true for 21 chemical methods of removal of pollutants using advanced 22 oxidation processes as well.…”
Section: Introductionmentioning
confidence: 98%
“…However, the waste is concentrated at the end of such 18 treatments instead of undergoing complete annihilation [1]. Then, 19 this concentrated waste is either incinerated or dumped on land 20 contributing to another type of pollution. The same is true for 21 chemical methods of removal of pollutants using advanced 22 oxidation processes as well.…”
Section: Introductionmentioning
confidence: 98%
“…15 Based on the historical industrial use as a white pigment, the photocorrosion of ZnS and especially the related darkening of such paints under sunlight irradiation have been observed already at the turn of the 19th to the 20th century. 16−18 In early reports the darkening of the pigments was ascribed to the formation of metallic Zn, 19 and ZnSO 4 and H 2 were postulated as other photocorrosion products. 19,20 It has been reported that the occurring degradation reactions strongly depend on the experimental conditions, e.g., the presence of water or oxygen, and on the synthesis temperature of the material and its structural properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Shortly later it was shown that UV light and the presence of water is necessary to observe this photocorrosion [77]. The first quantitative investigation by Platz and Schenk [78] revealed the additional formation of hydrogen, zinc sulfate and zinc hydroxide.…”
Section: ) Photocorrosionmentioning
confidence: 99%